Generational differences in the second and third wave feminism : Reasons and Results - Mezaouekh, Mohamed Aymen; Rakhrour, Oumelsaad; Guellil, Assia (University of Ammar Theledji -Laghouat, 2022)
Feminism is known for the huge changes it had witnessed during its long history. Yet, the conflict that occurred between the second and third waves marks a very important era. The second wave feminism fought to liberate women‘s body; meanwhile the third wavers came with the urge to liberate their actions. This exploratory-analytical research aims to explore this conflict and shed light on the reasons behind it, its consequences on modern feminism as well as its relationship with the theory of generations. According to the main results drawn from this research, the differences that emerged during the third wave are the reason behind problems within the movement, such as porn industry and the legalization of prostitution under the name of body freedom in addition to the promotion of mono-sexual marriage